Incidental Ga-68-Prostate-Specific Membrane Antigen Uptake in Compression Fracture of a Vertebral Body - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Prostate-specific membrane antigen (PSMA) is a membrane glycoprotein, which is overexpressed in prostate cancer cells. With its wide use, there is a growing number of case reports describing non-prostate cancer-related benign and malignant lesions showing increased Ga-68-PSMA uptake. We herein present the case of an 89-year-old man with prostate cancer who was referred for Ga-68-PSMA PET/CT for restaging, which revealed incidental Ga-68-PSMA uptake in compression fracture of a vertebral body. This case demonstrates that PSMA expression may occur in acute compression fractures, and it can be a potential pitfall when reporting Ga-68-PSMA PET/CT images.
Keywords: Ga-68-PSMA; compression fracture; PET/CT; prostate cancer; PROSTATE-CANCER; PATTERNS; PET/CT